Supervision and Facility Availability as Determinants of Midwives’ Performance in Recording and Reporting Local Area Monitoring of Maternal and Child Health - Oktaviani, Oktaviani; Natalina, Riny (Jurnal Penelitian Kesehatan SUARA FORIKES, 2026)
Improving the health of mothers, newborns, and children through various maternal and child health (MCH) initiatives is an essential priority. One important strategy to enhance the quality of MCH services is improving the quality of recording and reporting data through the Local Area Monitoring of Maternal and Child Health. Midwives’ performance plays a crucial role in ensuring the accuracy and completeness of these recording and reporting activities. This study aimed to analyze factors associated with midwives’ performance in recording and reporting PWS KIA data in the working area of Panarung Primary Health Center. This study employed a cross-sectional design. The sample consisted of 20 midwives working in the Panarung Primary Health Center area, selected using a total sampling technique. Data were collected using a structured questionnaire. The relationships between variables were analyzed using the Fisher’s exact test. The analysis showed that supervision (p = 0.03) and facility availability (p = 0.02) were significantly associated with midwives’ performance. In contrast, age (p = 1.00), education level (p = 0.45), length of service (p = 1.00), perception (p = 0.65), motivation (p = 1.00), and workload (p = 1.00) were not significantly associated with midwives’ performance. In, conclusion, midwives’ performance in recording and reporting data of the Local Area Monitoring of Maternal and Child Health is significantly associated with supervision and the availability of facilities.Keywords: supervision; facilities; midwives’ performance; maternal and child health